Cycles and Multiple Equilibria in the Market for Durable Lemons - Maarten C.W. Janssen; Vladimir Karamychev (Tinbergen Institute, 2000)
We investigate the nature of market failure in a dynamic version ofAkerlof (1970) where identicalcohorts of a durable good enter the market over time. In the dynamicmodel, equilibria withqualitatively different properties emerge. Typically, in equilibriaof the dynamic model, sellerswith higher quality wait in order to sell and wait more than sellersof lower quality. Our main resultis that for any distribution of quality that there exist an infinitenumber of cyclical equilibria whereall goods are traded within a certain number of periods afterentering the market.
Keywords: D82; 330; Dynamic Trading; Asymmetric Information; Entry; Durable Goods; Dauerhafte Konsumgüter; Produktqualität; Gleichgewichtstheorie; Theorie